The Influence of the Demonstration Method Used by Teacher on The Reading Ability (Qualitative Research at 5th Grade Students at SDN BANJARSARI - Siti Nopita; Putri Pujiyawati; Siti Agnia Hadean; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to examine the influence of the demonstration method on the English reading ability of 5th-grade students at SDN Banjarsari 02. The background of this research is the low English reading ability of students, despite the teacher having tried various methods. The demonstration method was chosen because it is believed to enhance student understanding and participation. This qualitative descriptive study involved 36 fifth-grade students. Data were collected through observation, a reading comprehension test (5 multiple-choice questions), questionnaires, and semi-structured interviews. The results showed that the demonstration method effectively improved students' understanding of explicit information in the text, but difficulties remained in understanding implicit information and details. Students rated the demonstration method as enjoyable and motivating, although some doubted its effectiveness in improving reading ability. Challenges encountered included student focus and the classroom environment. In conclusion, the demonstration method is beneficial but needs to be complemented by other strategies to improve inferential understanding and address learning environment constraints.